Survey of student attitudes towards digital simulation technologies at a dental school in China. (4th April 2016) - Ren, Q.; Wang, Y.; Zheng, Q.; Ye, L.; Zhou, X. D.; Zhang, L. L.
Abstract: Introduction: Digital simulation technologies have become widespread in healthcare education, especially in dentistry; these technologies include digital X‐ray images, digital microscopes, virtual pathology slides and other types of simulation. This study aimed to assess students' attitudes towards digital simulation technologies at a large, top‐ranked dental school in China, as well as find out how students compare the digital technologies with traditional training methods. Methods: In April 2015, a custom‐designed questionnaire was distributed to a total of 389 students who had received digital technology and simulation‐based training in West China Dental School during 2012–2014. Results: Results of a cross‐sectional survey show that most students accept digital simulation technology; they report that the technology is stimulating and facilitates self‐directed and self‐paced learning. Conclusion: These findings, together with the objective advantages of digital technology, suggest that digital simulation training offers significant potential for dental education, highlighting the need for further research and more widespread implementation.